Effects of 200 Gy 60Co-γ Radiation on the Regulation of Antioxidant Enzymes, Hsp70 Genes, and Serum Molecules of Plutella xylostella (Linnaeus) - Xiaoxue Li; Lingyan Luo; Sengodan Karthi; Ke Zhang; Jianjun Luo; Qiongbo Hu; Qunfang Weng (Molecules, 2018)
The diamondback moth, Plutella xylostella (Linnaeus), is one of the notorious pests causing substantial loses to many cruciferous vegetables across the nations. The effects of 60Co-γ radiation on physiology of P. xylostella were investigated and the results displayed that 200 Gy irradiation significantly alters the antioxidant enzyme regulation in six-day-old male pupae of P. xylostella. First, in our research, we detected Oxidase system and stress response mechanism of irradiated pupae, the results displayed that 200 Gy irradiation significantly alters the antioxidant enzyme regulation in six-day-old male pupae of P. xylostella. The levels of superoxide dismutase (SOD) and catalase (CAT) were increased significantly in contrast the level of peroxidase (POD) and glutathione S-transferase (GST) were decreased in 12–24 h post-treatment. The heat shock proteins (Hsps) gene expression level was significant increasing, maximum > 2-folds upregulation of genes were observed in peak. However, they also had a trend of gradual recovery with development. Second, we detected the testis lactate dehydrogenase (LDH) and acid phosphatase (ACP) activity found that in male adults testis they increased significantly than control during its development. Thus the present research investigation highlights that the 60Co-γ radiation treatments alters the physiological development of diamondback moth. The results showed that 200 Gy dosage resulted in stress damage to the body and reproductive system of the diamondback moth.